Two dads / two moms: Defying and affirming the mom-dad family. The case of same-gender families in Slovenia - Ana Sobočan (Linköping University Electronic Press, 2013)
'Family' remains a site of ideological struggles. What constitutes a family and who can become/have/define a family is a matter of ongoing political and other debates and discourses. These become evident in the programmes of political parties, for example, as well as in the agendas in family legislation and social welfare policies, even in the changes in sociological textbooks, and so forth. Families where two male or female partners are parenting together are simultaneously gaining visibility in the public space (and legislation in certain countries) and their children are becoming central in different discursive practices, where their presumed interests are used in argumentations of (mostly) the opponents and advocates of equal rights for all family constellations. A vast research body of studies about lesbian and gay families (begun in the 1970s) contributes to the visibility and understanding of a variety of forms in which families are created. As Malmquist and Zetterqvist Nelson write, it is "important to understand 'family' as something that is continuously performed - 'doing family' - rather than a specific structure - 'the family'" Weeks, Heaphy, and Donovan claim that it is exactly non-heterosexuals who are at the forefront of wider changes to family life, and Haimes and Weiner, for example, write how non-heteronormative family models present an important challenge to the heteronormative model.